Self-Assembly of Lysine-Based Dendritic Surfactants Modeled by the Self-Consistent Field Approach - Shavykin, O. V; Leermakers, F. A. M; Neelov, I. M; Darinskii, A. A (Langmuir, 2018)
Implementing a united atom model, we apply self-consistent field theory to study structure and thermodynamic properties of spherical micelles composed of surfactants that combine an alkyl tail with a charged lysine-based dendritic headgroup. Following experiments, the focus was on dendron surfactants with varying tail length and dendron generations G0, G1, G2. The heads are subject to acetylation modification which reduces the charge and hydrophilicity. We establish a reasonable parameter set which results in semiquantitative agreement with the available experiments. The critical micellization concentration, aggregation number, and micelle size are discussed. The strongly charged dendronic surfactants micelles are stable for generation numbers G0 and G1, for progressively higher ionic strengths. Associates of G2 surfactants are very small and can only be found at extreme surfactant concentration and salt strengths. Micelles of corresponding weaker charged acetylated variants exist up to G2, tolerate significantly lower salt concentrations, but lose the spherical micelle topology for G0 at high ionic strengths.